Effect of continuous infusion in alleviating pain during male urethral catheterization - Lijun Cao; Xin Qi; Dan Liu; Xincheng Mao; Liu Luo; Mengjiang Liu; Xinyi Wen; Chunhong Cui; Jia Qi; Junmei Xu; Yulong Cui (BMC Anesthesiology)
Abstract Aims The aim of this study was to explore whether continuous infusion causing lubrication can effectively alleviate pain during male urethral catheterization. Methods This prospective, multicenter, double-blinded study included 190 male patients scheduled for urethral catheterization. Patients were randomly allocated into four groups: Group A: the catheter was lubricated with paraffin; Group B: the catheter was lubricated with compound lidocaine gel; Group C: the pump continuously infusing with sterilized water; Group D: the pump continuously infusing with 2% lidocaine. The primary outcome was the visual analogue scale (VAS) scores. Statistical analysis system (SAS) (version 9.4) was used to perform all the statistical analyses. Significance for all results was set at P < 0.05. Results The VAS of Group D was the lowest (18.90 ± 11.44), followed by the Group C (33.00 ± 11.07), and the VAS of Group A was the highest (53.98 ± 14.76). There were significant differences in VAS in Group D compared to Group A(P < 0.0001), Group B(P < 0.0001) and Group C (P < 0.0001), Group C compared to Group A (P < 0.0001) and Group B(P < 0.0001), Group B compared to Group A (P < 0.0001), indicating that patients treated with lidocaine infusion (Group D) experienced significantly less pain than did those in the other three groups. Conclusions Continuous infusion with sterilized water during catheterization is an efficient method for lubricating the urethral mucosa; furthermore, infusion with 2% lidocaine provides better analgesia as well as lubrication. Trial registration The study protocol was registered in the Chinese Clinical Trial Registry (ChiCTR2300070866) ( https://www.chictr.org.cn/showproj.html?proj=194591 ) on Apr. 25th, 2023.